Pemanfaatan media pembelajaran dalam meningkatkan motivasi dan hasil belajar PAI di sekolah dan madrasah - Sartika, Fitria; Desriwita, Elni; Ritonga, Mahyudin (Universitas Negeri Yogyakarta, 2020)
This study discusses the use of instructional media in increasing motivation and learning outcomes of Islamic Religious Education in Schools and Madrasas. Learning media is an important thing used by teachers to attract interest and foster student motivation in learning, especially Islamic religious subjects, so that students easily understand the material presented without feeling bored and tired of listening to the teacher's submission. With the aim that PAI learning materials can really be understood and practiced by students after being studied at school and madrasa. The method used in this research is a quantitative qualitative approach that is described descriptively. The findings state that the RasulullÄh sebagai as an excellent educator has also used various forms of media in conveying Islamic education to friends, so that friends are able to understand the teachings of Islam properly and correctly. The results of the study of the use of instructional media show that learning media can provide an increase in student motivation, greatly assisting teachers in implementing the teaching and learning process to achieve the objectives of a learning material. The use of instructional media is also able to provide a great influence in improving student learning outcomes in PAI learning in schools and madrasas.